Cultural policy of the Tuvan People’s Republic and public festivities - Kuzhuget, Ailana K. (The New Research of Tuva, 2020)
The article discusses the main directions of the Tuvan People’s Republic state policy on holiday culture in the 1920s–30s, including the introduction of new types of festivities, such as rallies or demonstrations, and suppression and ultimate prohibition of traditional rituals and holiday. The new festivities aimed to reflect the changes in the social, political and economic life of the people of Tuva. For our sources, we rely on printed materials and previously unknown documents from the National Archives of the Republic of Tuva.As far as celebrations are concerned, the cultural policy of the PRT appeared a combination of various, often contradictory or even mutually exclusive, trends. It can be divided into two periods differing in the main orientation of the region’s internal policy. In the earlier period, 1920s, traditional holidays, including religious ones, were still allowed. Later, in the 1930s, Tuvan People’s Revolutionary Party pursued a new sociocultural policy which proclaimed drastic change and radical break with the past. Everything pertaining to the traditional culture: rituals and holidays, food and apparel, the yurt, even throat singing and the arts of woodcut and stone carving was labelled “backward”. Festivals were political, rather than cultural, events, and thus organizing them was the government’s responsibility, entrusted to ad hoc committees.Over a short period of time, Tuvan’s festival culture underwent drastic change.
Keywords: Tuvan People’s Republic; history of Tuva; Tuva; Tuvans; cultural policy; festival; public holiday; Socialist ideology